2010
DOI: 10.1111/j.1440-1797.2010.01287.x
|View full text |Cite
|
Sign up to set email alerts
|

Review: Differences in prescription between conventional and alternative haemodialysis

Abstract: SUMMARY AT A GLANCELonger hours dialysis has several challenges -one of these -modifying the dialysate composition is addressed in this article. ABSTRACT:There is growing interest worldwide in the beneficial effects of increasing the frequency and/or time of haemodialysis (HD) sessions. Alternative HD regimens to incorporate these changes, also called 'quotidian' HD schedules, likely offer advantages over conventional thrice-weekly HD. Alternative regimens include short-daily HD (typically performed 1.5-3 h, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
(113 reference statements)
1
6
0
Order By: Relevance
“…Moreover, 20 % of all our patients had albumin levels <30 g/dl and 31 % hemoglobin levels <10 g/dl, suggesting that our population is predisposed to malnutrition [ 21 , 23 ] and anemia [ 5 , 21 , 24 ]. The finding that 48 and 33.5 % of patients in the dDHD group had low hemoglobin and albumin levels, respectively, indicates, as reported in previous studies [ 9 , 18 , 21 , 24 , 36 ], that patients started DHD as an emergency because of their poor medical status which did not allow proposing thrice-weekly HD with long sessions. Our results showed that patients who started directly with DHD presented a higher risk of mortality (HR = 2.44; 95 % CI: 1.91–3.11), but paradoxically they had a better access to renal transplantation (HR = 2.03; 95 % CI: 1.38–3.0).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Moreover, 20 % of all our patients had albumin levels <30 g/dl and 31 % hemoglobin levels <10 g/dl, suggesting that our population is predisposed to malnutrition [ 21 , 23 ] and anemia [ 5 , 21 , 24 ]. The finding that 48 and 33.5 % of patients in the dDHD group had low hemoglobin and albumin levels, respectively, indicates, as reported in previous studies [ 9 , 18 , 21 , 24 , 36 ], that patients started DHD as an emergency because of their poor medical status which did not allow proposing thrice-weekly HD with long sessions. Our results showed that patients who started directly with DHD presented a higher risk of mortality (HR = 2.44; 95 % CI: 1.91–3.11), but paradoxically they had a better access to renal transplantation (HR = 2.03; 95 % CI: 1.38–3.0).…”
Section: Discussionsupporting
confidence: 69%
“…Additionally, the REIN registry includes also data on the treatment modalities as well as on the pre- and post-DHD treatment switches. Therefore, and differently from previous studies that only described the first RRT modality and/or the length of the pre-DHD period [ 16 , 18 , 22 , 28 , 33 ], we could analyze and describe all the RRT modality changes before switching to DHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New dialysis regimens have been developed and tested with the aim of improving the patients' quality of life and blood purification . For instance, some authors have shown that increasing the weekly frequency of dialysis sessions is the best regimen to mimic the kidney functional role, compared with haemodialysis (HD) three times/week . Several studies on daily haemodialysis (DHD) reported the positive effects of increasing the number of HD sessions per week on the control of blood pressure, uraemia and ventricular hypertrophy in patients with end stage renal disease (ESRD).…”
mentioning
confidence: 99%
“…3,4 For instance, some authors have shown that increasing the weekly frequency of dialysis sessions is the best regimen to mimic the kidney functional role, compared with haemodialysis (HD) three times/week. 3,[5][6][7] Several studies on daily haemodialysis (DHD) reported the positive effects of increasing the number of HD sessions per week on the control of blood pressure, 4,[8][9][10][11] uraemia 3,4 and ventricular hypertrophy [9][10][11] in patients with end stage renal disease (ESRD). On the other hand, DHD effects on mortality are less clear-cut.…”
mentioning
confidence: 99%